Experimental Stress Analysis for Materials and Structures Stress Analysis Models for Developing Design Methodologies - Freddi, Alessandro; Olmi, Giorgio; Cristofolini, Luca.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book summarizes the main methods of experimental stress analysis and examines their application to various states of stress of major technical interest, highlighting aspects not always covered in the classic literature. It is explained how experimental stress analysis assists in the verification and completion of analytical and numerical models, the development of phenomenological theories, the measurement and control of system parameters under operating conditions, and identification of causes of failure or malfunction. Cases addressed include measurement of the state of stress in models, measurement of actual loads on structures, verification of stress states in circumstances of complex numerical modeling, assessment of stress-related material damage, and reliability analysis of artifacts (e.g. prostheses) that interact with biological systems. The book will serve graduate students and professionals as a valuable tool for finding solutions when analytical solutions do not exist.
Introduction to Inverse Problems -- Introduction to the Application of Strain Gages -- Introduction to Photoelasticity -- Introduction to Holographic Interferometry -- Overview of Digital Image Correlation -- Static Stress Models -- Local Stress Models for Variable Loads -- Local Strain Models for Variable Loads -- Elementary Models for Stress Singularities -- Stress Models in Biomechanics -- Reliability Models Based on Experiments.
Keywords: Engineering; Physical measurements; Measurement; Continuum mechanics; Machinery; Biomedical engineering; Materials science; Engineering; Continuum Mechanics and Mechanics of Materials; Characterization and Evaluation of Materials; Machinery and Machine Elements; Measurement Science and Instrumentation; Biomedical Engineering; Electronic books